Creation of municipalities in Brazil: motivations, advantages and disadvantages (Revista Espinhaço, 2017)
Brazilian municipalism witnessed moments of relative autonomy and political constraints imposed by its constitutional history. The Federal Constitution of 1988, by granting greater autonomy to the federative units on the subject of emancipations, contributed to the occurrence of a new emancipationist outbreak in the country. Thus, in the course of the 1990s, 1,070 were created, most of them without financial means to support themselves. This paper aims to bring to the discussion emancipations throughout Brazilian constitutional history, and to analyze the motivations, advantages and disadvantages of the creation of new municipalities in Brazil after the Federal Constitution of 1988. The results showed that the emancipations were not point of agreement between different social segments. Several reasons have been identified, mainly political, economic and demographic. These can be summarized by the neglect of the administration of the municipality of origin, by the existence of an economic activity in the locality, by the large territorial extension of the municipality of origin, and by the growth of the local population. The quality of these emancipations can be measured through socioeconomic and demographic indicators. In general, there was an improvement in the social conditions of the inhabitants of emancipated localities. On the other hand, those who oppose emancipation affirm that the process has allowed the proliferation of small municipalities, which are not always the poorest, and are the ones that spend more per capita with the municipal legislature, making the burden on the municipalities proportionately greater.
Keywords: municipalities; district emancipations; advantages and disadvantages; federal constitutions